Audit reports timeliness: Empirical evidence from Tunisia - Imen Fakhfakh Sakka; Anis Jarboui (Cogent Business & Management, 2016)
Timeliness of corporate annual financial reports is considered to be a critical and important factor affecting the usefulness of information that is made available to external users. The purpose of this paper is to examine the relationship between corporate governance, external auditor's characteristics index, and timeliness in light of the recent amendments to the Financial Security Law (2005) in Tunisia. The paper uses panel data methodology of 28 Tunisian companies listed on the Tunisian Stock Exchange over the period 2006–2013. This study concludes that the good structures of corporate governance play a key role in improving the quality of timeliness of financial reports. As for the empirical tests, they appear to indicate that whenever the audit report publication date proves to be short, the external auditor's characteristics index is discovered to be high.
Keywords: 650